(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the productive performance, organosomatic indices and liver-intestinal histomorphometric parameters of Nile tilapia (Oreochromis niloticus) juveniles, fed diets containing probiotics (yeast - Saccharomyces cerevisiae) and reared at different densities of storage. In this experiment, 450 juveniles of tilapia (2.9 ± 0.23 g) were distributed in 18 experimental units arranged in RAS and arranged in a randomized block design in a 2x3 factorial scheme. These animals were fed two diets, the first without yeast and the second containing 0.1% yeast inclusion and distributed in three stocking densities of 15, 25 and 35 fish / m3 (500, 833 and 1166 fish / m3). There was an improvement in the oxygenation of the medium with the use of yeast, as well as in the lowest stocking densities evaluated (15 and 25 fish / m³). However, lower specific growth rates and higher viscerosomatic index were observed in animals supplemented with 0.1% yeast. For the average area of hepatocytes, there was an interaction between the evaluated factors (use of probiotic x storage density), where the best values were found in the lowest storage densities (15 and 25 fish / m³), regardless of use or not of the probiotic. It is recommended to use a stocking density of 15 to 25 fish / m³ and a supplementation of 0.1% with yeast as a probiotic, in order to improve liver health and oxygenation of the water used to grow Nile tilapia juveniles cultivated in RAS.